2022
DOI: 10.1007/s40273-022-01168-0
|View full text |Cite|
|
Sign up to set email alerts
|

Cost-Effectiveness Analysis of Molnupiravir Versus Best Supportive Care for the Treatment of Outpatient COVID-19 in Adults in the US

Abstract: Background and aims Coronavirus disease 2019 (COVID-19) imposes a substantial and ongoing burden on the US healthcare system and society. Molnupiravir is a new oral antiviral for treating COVID-19 in outpatient settings. This study evaluated the cost-effectiveness profile of molnupiravir versus best supportive care in the treatment of adult patients with mild-tomoderate COVID-19 at risk of progression to severe disease, from a US payer's perspective. Methods The model was developed using a decision tree for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 39 publications
0
21
0
Order By: Relevance
“…However, as with all trials, the demographic and disease characteristics of the population enrolled may differ from those seen in other health systems, particularly in terms of vaccination status. As noted in a recent analysis of another COVID-19 treatment, molnupiravir, 13 COVID-19 studies are inherently challenged by the evolution of the pandemic, particularly in relation to new viral strains and variability in SOC. However, subgroup analyses of the TOGETHER trial uniformly demonstrate favorable results for fluvoxamine, suggesting that heterogeneity of patient characteristics is unlikely to undermine the validity of the conclusions of this analysis, though further study of alternative SOC models is warranted.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, as with all trials, the demographic and disease characteristics of the population enrolled may differ from those seen in other health systems, particularly in terms of vaccination status. As noted in a recent analysis of another COVID-19 treatment, molnupiravir, 13 COVID-19 studies are inherently challenged by the evolution of the pandemic, particularly in relation to new viral strains and variability in SOC. However, subgroup analyses of the TOGETHER trial uniformly demonstrate favorable results for fluvoxamine, suggesting that heterogeneity of patient characteristics is unlikely to undermine the validity of the conclusions of this analysis, though further study of alternative SOC models is warranted.…”
Section: Discussionmentioning
confidence: 99%
“… 12 However, the approach differs from a recent analysis of molnupiravir, which used reduced rates of care escalation for treated patients based on post hoc analyses of the trial data. 13 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cost-effectiveness analyses from Hong Kong and USA analysing data from large electronic health databases showed that the use of SARS-CoV-2 oral antivirals, vs. symptomatic care, in outpatient setting reduced healthcare costs and increased quality-adjusted life years, by reducing subsequent hospital admissions, readmissions and long-term sequelae [ 12 , 20 ].…”
Section: Treatment Of Mild-to-moderate Covid-19 Disease In the Outpat...mentioning
confidence: 99%
“…Being a repurposed drug, fluvoxamine, which was first approved by the FDA in 1994 (trade name: Luvox), has the advantage of decades of safety data surrounding its use. Unlike molnupiravir and paxlovid where a treatment course costs approximately 700 and 500 USD, respectively ( Goswami et al, 2022 ; Morrison Ponce et al, 2022 ), fluvoxamine is accessible at 4 USD per course ( Wang et al, 2021 ). Remdesivir is also expensive at over 2000 USD per 5-day treatment course ( Carta and Conversano, 2021 ).…”
Section: Introductionmentioning
confidence: 99%